Analysis of Transformer Oil Condition of Dissolved Gas Analysis (DGA) Testing Results with Modified Conventional Methods - Budhihadi, Randy Purnawan; Sudiarto, Budi (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
Power transformers are one of the most widely used important components in the electric power system. Dissolved Gas Analysis (DGA) testing is used to diagnose transformer failures before more severe damage occurs by analyzing gas indicators dissolved in transformer oil through several methods, one of which uses conventional methods. However, based on most of the tests conducted by researchers, the detection accuracy of the conventional method is still quite low. Therefore, this research has the main objective of identifying the weaknesses of one of the conventional methods, namely the Rogers Ratio method. This research method uses modifications to the fault diagnosis flow chart which is then applied in the interpretation of DGA test results on power transformers in the case of the GSUT #1 20/11 kV Transformer of Manokwari Gas Engine Power Plant (GEPP). Based on the results of this research, the previous method cannot diagnose the fault (Undetermined) while after being modified it can diagnose the “Thermal Fault 150-200OC. When compared with other conventional methods that have been tested such as the interpretation of the Duval Triangle method, the results of diagnosing “Thermal Fault < 300OC”, it means that in general can be known that there has been a thermal disturbance in the internal transformer at temperatures below 300OC. Thus the results of the modified interpretation of the Rogers Ratio method are better than before so that it can be applied as an additional technique for interpreting DGA test data